2003
DOI: 10.1002/pssc.200303519
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth kinetics on the indium distribution during MOVPE growth of GaInN quantum wells

Abstract: The composition and thickness of GaInN quantum wells (QWs) determines the luminescence properties of GaInN/GaN-based optoelectronic devices. The In distribution is characterized by considerable inhomogeneities on two spatial scales. Variations of locally averaged In concentrations and QW thickness on a "large" scale of several 10 nm along the QW occur in addition to small clusters with high In concentrations up to 100% and sizes of only a few nanometers. In the present work, we investigated the influence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The small interaction between Ga flow rate and temperature can be seen as a kink in the plane for the graph in Figure 3a It is well known that the growth temperature and Ga flow rate will affect the emission wavelength of InGaN based layers 18 , however the interaction between the two has not been studied previously. The effect of the growth kinetics on the indium distribution in InGaN quantum wells was studied previously 19 and it was found that there is a large effect of the growth rate on the In distribution inside the well. At lower growth rates there is a higher degree of long range clustering of In atoms, but that the size of small agglomerates was not affected.…”
Section: Resultsmentioning
confidence: 98%
“…The small interaction between Ga flow rate and temperature can be seen as a kink in the plane for the graph in Figure 3a It is well known that the growth temperature and Ga flow rate will affect the emission wavelength of InGaN based layers 18 , however the interaction between the two has not been studied previously. The effect of the growth kinetics on the indium distribution in InGaN quantum wells was studied previously 19 and it was found that there is a large effect of the growth rate on the In distribution inside the well. At lower growth rates there is a higher degree of long range clustering of In atoms, but that the size of small agglomerates was not affected.…”
Section: Resultsmentioning
confidence: 98%
“…There is many contradictory experimental data on Insegregation in InGaN quantum wells. From our experience and the works of Hahn et al [16], we can issue a list of the main obstacles, why the task of growing uniform InGaN quantum wells is so difficult:…”
Section: Indium Segregationmentioning
confidence: 99%